2009
DOI: 10.1007/s11606-009-1060-3
|View full text |Cite
|
Sign up to set email alerts
|

Violent Patient Behavior Is Associated with Bodily Pain and a High Burden on Informal Caregivers

Abstract: BACKGROUND: There have been no studies of the relationship between violent behavior by older patients and the physical and mental health of caregivers. OBJECTIVE:To evaluate the influence of violent behavior in vulnerable elderly patients on bodily pain and caregiver burden in their informal caregivers. DESIGN:Cross-sectional study. SUBJECTS:One hundred thirty-seven patients aged ≥40 years old with limited activity and mobility in ten facilities providing home-care services in Japan.MEASUREMENTS: Degree of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…Another interesting finding is that caregivers who provide only home care reported more severe emotional responses toward the care recipient and frustration toward the caring situation, which was reflected in the rising action category exploring the psychological and emotional challenges concretely. This insight can also be related to the past literature pointing to psychologically and physically abusive behaviors occurring in the informal caregiving context [ 31 - 33 ], suggesting that the type of care (in-home only vs shared care with respite/or a day center) could be related to more severe reactions.…”
Section: Discussionsupporting
confidence: 62%
“…Another interesting finding is that caregivers who provide only home care reported more severe emotional responses toward the care recipient and frustration toward the caring situation, which was reflected in the rising action category exploring the psychological and emotional challenges concretely. This insight can also be related to the past literature pointing to psychologically and physically abusive behaviors occurring in the informal caregiving context [ 31 - 33 ], suggesting that the type of care (in-home only vs shared care with respite/or a day center) could be related to more severe reactions.…”
Section: Discussionsupporting
confidence: 62%
“…A previous study suggested that the reasons caregivers hesitate to provide oral care services were due to physical violence from their client and the client not opening his or her mouth . Moreover, most studies suggest that violence is a component of the general caregiver burden . Overall, our results concur with previous reports that Risk related burden plays an important role in oral health‐related caregiver burden.…”
Section: Discussionmentioning
confidence: 99%
“…Three main components that affect these individuals have been identified: the impact of care, the interpersonal burden, and self‐efficacy expectations . Recent studies have described different factors associated with the level of caregiver burden: the hours of providing care, deficient psychosocial support, and a poor work or financial situation; other patient‐dependent factors are emotional state, level of incapacity, violent behavior, or urinary incontinence . Nevertheless, the relative importance of these factors is still unclear in relation to predicting CSS .…”
Section: Discussionmentioning
confidence: 99%